1978
DOI: 10.1128/mmbr.42.3.529-576.1978
|View full text |Cite
|
Sign up to set email alerts
|

Head morphogenesis of complex double-stranded deoxyribonucleic acid bacteriophages.

Abstract: Following the nomenclature of Casjens and King (52), "gp" means gene product, and it is used as a prefix to the gene name; i.e., gpB is the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
1

Year Published

1981
1981
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(66 citation statements)
references
References 264 publications
(670 reference statements)
0
65
1
Order By: Relevance
“…Many new insights were obtained by a detailed analysis of new data from lambdoid phages, especially of head and lysis genes (Casjens et al, 1992). It was concluded that (1) genes with related functions clustered together; (2) genes of different phages could be homologous (related) or analogous (encoding different proteins with identical functions); (3) gene orders were more conserved than nucleotide sequences; Hemphill and Whiteley, 1975;Murialdo and Becker, 1978;Stewart, 1993Bishai and Murphy, 1988Bertani and Six, 1988Casjens et aZ., 1992;Daniels et al, 1983;Drexler, 1988;Harshey, 1988;Hausmann, 1988;Kutter et al, 1994;Poteete, 1988;Yarmolinski and Stern berg, 1988;Ziegelin and Lanka, 1995P22, T7 Esposito et al, 1996Kodaira et al, 1997Mikkonen, 1996Arendt et al, 1994Lubbers et al, 1995;Schouler et al, 1994;Van Sinderen et al, 1996Hatfull pt al., 1993Bidnenko et al, 1989Sik and Orosz, 1971Kretschmer and Egan, 1975Shinomiya and Ina, 1989 Cp-1 Garcia et at., 1997Klaus et al, 1992 (4) tailed phages could form "quasi-species" with little sequence similarity, but the same gene orders and transcription patterns; and (5) tailed phages routinely acquired genes from their hosts, phages, or other sources. It was also noted that the arrangement of portal, scaffolding, and capsid protein genes was similar in phages T4, T7, and $29 and that a tailed Staphylococcus phage showed the same gene order of lysogeny sites (att, int, xis) as lambdoid phages.…”
Section: Functional Genomic Mapsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many new insights were obtained by a detailed analysis of new data from lambdoid phages, especially of head and lysis genes (Casjens et al, 1992). It was concluded that (1) genes with related functions clustered together; (2) genes of different phages could be homologous (related) or analogous (encoding different proteins with identical functions); (3) gene orders were more conserved than nucleotide sequences; Hemphill and Whiteley, 1975;Murialdo and Becker, 1978;Stewart, 1993Bishai and Murphy, 1988Bertani and Six, 1988Casjens et aZ., 1992;Daniels et al, 1983;Drexler, 1988;Harshey, 1988;Hausmann, 1988;Kutter et al, 1994;Poteete, 1988;Yarmolinski and Stern berg, 1988;Ziegelin and Lanka, 1995P22, T7 Esposito et al, 1996Kodaira et al, 1997Mikkonen, 1996Arendt et al, 1994Lubbers et al, 1995;Schouler et al, 1994;Van Sinderen et al, 1996Hatfull pt al., 1993Bidnenko et al, 1989Sik and Orosz, 1971Kretschmer and Egan, 1975Shinomiya and Ina, 1989 Cp-1 Garcia et at., 1997Klaus et al, 1992 (4) tailed phages could form "quasi-species" with little sequence similarity, but the same gene orders and transcription patterns; and (5) tailed phages routinely acquired genes from their hosts, phages, or other sources. It was also noted that the arrangement of portal, scaffolding, and capsid protein genes was similar in phages T4, T7, and $29 and that a tailed Staphylococcus phage showed the same gene order of lysogeny sites (att, int, xis) as lambdoid phages.…”
Section: Functional Genomic Mapsmentioning
confidence: 99%
“…The literature on phage morphogenesis is abundant and has been the subject of a book (DuBow, 1981) and many excellent reviews, a few of which are cited here (Berget and King, 1983;Black et al, 1994;Casjens and Hendrix, 1988;Casjens and Kmg, 1975;Hendrix, 1985;Hendrix and Garcea, 1994;Kellenberger, 1990;Kellenberger and Wunderli-Allenspach, 1995;Murialdo and Becker, 1978;Wood and King, 1979).…”
Section: Particle Assemblymentioning
confidence: 99%
“…Assembly of the dsDNA bacteriophages, such as X, T4 or P2 is a complex process involving cooperation of many proteins (for reviews, see Murialdo and Becker, 1978;Casjens, 1985;Carrascosa, 1986;Casjens and Hendrix, 1988). It starts with the formation of an initiation complex, containing the connector which will give rise to the head-tail connection, upon which the main capsid proteins are assembled.…”
Section: Introductionmentioning
confidence: 99%
“…The procapsid genes in lambda encode the portal protein (gpB), the major capsid protein (gpE), the scaffolding protein (gpNu3), and the viral protease (gpC) (Daniels et al, 1983). Twelve copies of the portal protein assemble into a dodecameric ring, chaperoned by the scaffolding protein and host groELS ( Figure 3) (Kochan, Carrascosa, & Murialdo, 1984;Murialdo & Becker, 1978). While not rigorously proven, it is likely that portal assembly nucleates capsid shell assembly in vivo, serving as a platform for co-polymerization of the major capsid protein and the scaffolding protein to afford an icosahedral shell (Hendrix & Casjens, 1975;Murialdo, 1979).…”
Section: Bacteriophage Lambda Biologymentioning
confidence: 99%